Synthesis, Cytotoxicity, and Pro-Apoptosis Activity of Etodolac Hydrazide Derivatives as Anticancer Agents - ŞENER, AZİZE; ÖZSAVCI, DERYA; BİNGÖL ÖZAKPINAR, ÖZLEM; SÜZGÜN, PELİN; ÖZBAŞ, SUNA; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (WILEY-V C H VERLAG GMBH, 2013)
Etodolac hydrazide and a novel series of etodolac hydrazide-hydrazones 315 and etodolac 4-thiazolidinones 1626 were synthesized in this study. The structures of the new compounds were determined by spectral (FT-IR, 1H NMR, 13C NMR, HREI-MS) methods. Some selected compounds were determined at one dose toward the full panel of 60 human cancer cell lines by the National Cancer Institute (NCI, Bethesda, USA). 2-(1,8-Diethyl-1,3,4,9-tetrahydropyrano[3,4-b]indole-1-yl)acetic acid[(4-chlorophenyl)methylene]hydrazide 9 demonstrated the most marked effect on the prostate cancer cell line PC-3, with 58.24% growth inhibition at 105M (10 mu M). Using the MTT colorimetric method, compound 9 was evaluated in vitro against the prostate cell line PC-3 and the rat fibroblast cell line L-929, for cell viability and growth inhibition at different doses. Compound 9 exhibited anticancer activity with an IC50 value of 54 mu M (22.842 mu g/mL) against the PC-3 cells and did not display any cytotoxicity toward the L-929 rat fibroblasts, compared to etodolac. In addition, this compound was evaluated for caspase-3 and Bcl-2 activation in the apoptosis pathway, which plays a key role in the treatment of cancer.
Keywords: Apoptosis; Etodolac; Hydrazide-hydrazone; PC-3 prostate cancer cell line; 4-Thiazolidinone; NATIONAL-CANCER-INSTITUTE; ANTIMYCOBACTERIAL ACTIVITY; BIOLOGICAL-ACTIVITIES; POTENTIAL ANTITUMOR; IN-VITRO; DRUG DISCOVERY; CYCLOOXYGENASE-2; PROSTATE; INHIBITOR; CELLS